Bacillus Calmette-Guerin (BCG) infections following intravesical BCG immunotherapy: a systematic review protocol - Roberta Monardo; Sana Arif; Aparna Rege; Erin Simon; Leila Ledbetter; Arthur W. Baker; Jason Stout; Manuela Carugati (Systematic Reviews)
Abstract Background Although intravesical Bacillus Calmette-Guerin (BCG) immunotherapy usually exhibits a favorable safety profile, it can lead to the development of BCG infections, both localized and disseminated. Understanding of BCG infections following intravesical BCG immunotherapy is limited because of the lack of consensus definitions of BCG infections and limited post-instillation follow-up. We aim to perform a systematic review of the literature of BCG infections following intravesical BCG immunotherapy to elucidate the epidemiology, risk factors, and outcomes of BCG infections. Methods Systematic review of peer-reviewed published articles that describe the treatment of one or more persons with intravesical BCG and the occurrence of BCG infections among these patients. No temporal, geographic, or demographic limitations will be applied. Animal studies will be excluded. Gray literature, editorials, and comments will be excluded. Information sources will include the following databases: MEDLINE, Embase, and Web of Science. A search concept representing BCG and intravesical administration will be applied after validation against a set of pre-selected articles. Screening and data extraction will be performed in duplicate by two independent reviewers. Disagreements will be resolved by a third independent reviewer. The methodological quality of studies will be assessed using the Mixed Methods Appraisal Tool. A narrative synthesis of the extracted data will be provided in line with the guidance from the Centre for Reviews and Dissemination. The quality of evidence for all outcomes will be judged using the Grading of Recommendations Assessment, Development, and Evaluation working group methodology. Discussion The data generated by this review will assist clinicians in managing BCG-infected patients and inform future research efforts. Systematic review registration In accordance with international guidelines, our systematic review protocol was submitted for registration with the International Prospective Register of Systematic Reviews (PROSPERO) on February 26, 2024.